Political Communication as Organizational or Actor-Theoretical Finding in The Communication Between Politicians and Citizens in Social-Media - Ahmad Ismail TAHIR (Communications of International Proceedings, 2023)
Political communication as participation of citizens has become even broader due the expansion of communication possibilities with digital media and WEB-2.0, self-generated content in social-media on internet has become even more important for a social science analysis. The research results to date have concentrated on quantitative methods that look at the frequency of political communication and focus on the recipients in analysis. However, it is also important to look at the politicians' side, as a change of perspective makes comparative research in political communication increasingly possible. A qualitative research was conducted with German local politicians in the district of Herford in form of key question interviews under the research question 'How do politicians reflect on their political communication in social networks with citizens? The objective was to define communication in order to show whether politicians orientate their communication according to actor or organisation-theory. The analysis of the statements shows that politicians base their content very strongly on party guidelines.
Keywords: political communication; actor theory; organisation theory; election campaign